Research on Cross-Cultural Conflict Management in Chinese Enterprises Under the Belt and Road Initiative by Integrating Excellent Traditional Chinese Culture - Yajuan, Zhou; Minglang, Cao; Jiayue, Li (Advances in Social Sciences Research Journal, 2025)
This study innovatively integrates Confucian culture and the concept of a "community of shared future for mankind" into cross-cultural conflict management research. By using the cultural integration approach of cross-cultural conflict theory as a breakthrough, the study adopts the "Western framework with embedded Chinese elements" method. This approach imparts new cultural connotations to Confucianism and integrates them into Western management theories, thus forming a new cultural integration framework. This framework includes: "righteousness" based on corporate social responsibility, "benevolence" based on business ethics, "ritual" based on institutional theory, "wisdom" based on organizational learning, "trust" based on social network theory, and "moderation" based on stakeholder theory. The goal is to realize a shared cultural and interest community in multinational enterprises. This system explores the understanding and coexistence between diverse cultures by reinterpreting the meanings of "benevolence," "righteousness," "ritual," "wisdom," "trust," and "moderation," promoting "equal dialogue" and mutual prosperity among multicultural communities in multinational enterprises. Through equal dialogue and interaction, cultural differences and disputes can be resolved, achieving the ideal corporate cultural atmosphere of "all things grow together without harming each other, and all paths can coexist without contradiction."